Cyto-Histological Manifestations of the Apoptotic Process in the Prepubescent Mouse Ovary (14-17 days) - Liliana Petculescu-Ciochina; Gabi Dumitrescu; Nicolae Păcala; Dorel Dronca; Adela Marcu; Ioan Bencsik (Scientific Papers Animal Science and Biotechnologies, 2023)
Follicular atresia is a process commonly encountered at ovarian level that limits the number of ovulations and, respectively, the reproductive potential of a female. Ovarian cells’ death is essential for maintaining homeostasis of this organ and is based on an apoptotic mechanism that ensures selection of the dominant follicle and the disappearance of follicles in excess. The present study evaluates the incidence of morphological changes specific for this process in the prepubescent mouse ovary by applying optical microscopy techniques. Microscopic analysis was performed on sections of ovarian tissue from mice females’ line NMRI aged 14-17 days. The results show, at this age, significant morphological changes at cellular level, specific for apoptotic process, as condensation and fragmentation of the genetic material, vacuolization of cell cytoplasm, destabilization of cell adhesion junctions and appearance of wide intercellular spaces, invasion of created spaces with infiltrated leukocytes, formation of apoptotic bodies.